Field and hot electron-induced degradation in GaN-based power MIS-HEMTs. (September 2017) - Tajalli, Alaleh; Meneghini, Matteo; Rossetto, Isabella; Moens, Peter; Banerjee, Abhishek; Zanoni, Enrico; Meneghesso, Gaudenzio
Abstract: We investigate the degradation of AlGaN/GaN MIS-HEMTs submitted to gate step-stress experiments, and demonstrate the existence of field- and hot-electron induced processes. When the devices are submitted to gate-step stress with high VDS  > 50 V, four different regimes are identified: (i) for VGS  < − 10 V, no significant degradation is observed, since the devices are in the off-state; (ii) for − 10 V < VGS  < 0 V, hot electrons flow through the channel, as demonstrated by the (measurable) electroluminescence signal. These hot electrons can be trapped within device structure, inducing an increase in the threshold voltage. (iii) for VGS  > 0 V, the density of hot electrons is significantly reduced, due to the increased interface scattering and device temperature. As a consequence, EL signal drops to zero, and the electrons trapped during phase (ii) are de-trapped back to the channel, where they are attracted by the high 2DEG potential. (iv) Finally, for VGS  > 5 V, a significant increase in threshold voltage is detected. This effect is observed only for high positive voltages, i.e. when a significant leakage current flows through the gate. Such gradual degradation is ascribed to the injection of electrons from the 2DEG to the gate insulator, which is a field-driven effect. These results were obtained by combined electrical and optical characterization carried out at different voltages during the step stress.